2006
DOI: 10.3168/jds.s0022-0302(06)72516-4
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Administration of Glutamine Modulates Acute Phase Response in Postparturient Dairy Cows

Abstract: The objective of this study was to investigate whether administration of L-Gln would affect mediators of acute phase response in postparturient dairy cows. Twenty-four multiparous Holstein cows were blocked by the expected day of calving and randomly assigned to 1 of the 3 treatment groups (n = 8/group): 1) i.v. infusion of 10 L of 0.85% NaCl (control), 2) i.v. infusion of 106, or 3) 212 g/d of L-Gln mixed with 10 L of 0.85% NaCl solution; each treatment was given 8 h/d for each of 7 consecutive days starting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 23 publications
(22 reference statements)
8
25
0
1
Order By: Relevance
“…Therefore, further studies are warranted to verify the appropriate dose of Gln for steers. This study showed that Gln supplementation significantly increased LBP, which was in accordance with the study of Jafari et al (2006) where dairy cows were infused with 106 g/d and 212 g/d Gln. LBP can promote LPS to transfer to CD-14 to activate mononuclear macrophages and endothelial cells, which in turn activates Kupffer cells in liver to clear LPS via Toll-like receptors-4 (Purohit et al 2008).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Therefore, further studies are warranted to verify the appropriate dose of Gln for steers. This study showed that Gln supplementation significantly increased LBP, which was in accordance with the study of Jafari et al (2006) where dairy cows were infused with 106 g/d and 212 g/d Gln. LBP can promote LPS to transfer to CD-14 to activate mononuclear macrophages and endothelial cells, which in turn activates Kupffer cells in liver to clear LPS via Toll-like receptors-4 (Purohit et al 2008).…”
Section: Discussionsupporting
confidence: 77%
“…LBP can promote LPS to transfer to CD-14 to activate mononuclear macrophages and endothelial cells, which in turn activates Kupffer cells in liver to clear LPS via Toll-like receptors-4 (Purohit et al 2008). Furthermore, LBP can transfer LPS to serum lipoproteins, such as low-density lipoprotein (LDL) and highdensity lipoprotein (HDL), for clearing LPS from the bloodstream (Jafari et al 2006). Ceciliani et al (2012) indicated that high concentrations of LBP play an anti-inflammatory role, thus LBP can be regarded as a defense strategy against LPS in disproportionate inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serum amyloid A is a family of proteins encoded in a multigene complex and is one of the acute-phase reactants in response to infection, inflammation, and trauma (Jensen and Whitehead, 1998). Serum amyloid A in periparturient dairy cows was measured by ELISA and it was found to increase dramatically after calving (Meglia et al, 2005;Jafari et al, 2006). In our study, isoforms of serum amyloid A were found to be altered in plasma before calving in cows with or without new intramammary infection.…”
Section: Discussionmentioning
confidence: 49%
“…No entanto, a dose utilizada não atenuou as lesões decorrentes de I/R, devendo-se considerar doses maiores para tal finalidade. Na avaliação da diminuição da resposta inflamatória pós-parto em bovinos leiteiros, a glutamina foi utilizada nas doses de 159 e 319mg/ kg, tendo ambas igual eficácia (Jafari et al 2006).…”
Section: Discussionunclassified